Stem Cell-Associated Proteins and Extracellular Matrix Composition of the Human Atrioventricular Junction - Thorsell, Annika; Sjölin, Linnéa; Berger, Evelin; Jeppsson, Anders; Oldfors, Anders; Rotter Sopasakis, Victoria; Vukusic, Kristina (Cells (Basel, Switzerland), 2024)
The human heart regenerates slowly through life, but how new cells are generated is mostly unknown. The atrioventricular junction (AVj) has been indicated as a potential stem cell niche region. Little is known about the protein composition of the human AVj. To map the extracellular matrix (ECM) and expression of stem cell-related biomarkers, this study compares protein and gene expression patterns in AVj and Left Ventricular (LV) tissues. Biopsies were collected from 15 human hearts. Global quantitative proteomics and mRNA sequencing were used to identify differentially expressed proteins and altered genes. Of the total 4904 identified proteins, 1138 were differently expressed between the AVj and LV. While the top proteins in LV were involved in cardiac motor function and energy regulation, the AVj displayed proteins associated with early cardiomyocyte development, differentiation, proliferation, migration, and hypoxia. Furthermore, several developmental signalling pathways, including TGF-β, TNF, WNT, Notch, and FGF, were represented. RNA-seq data verified that the expressed genes were involved with differentiation, cell growth, proliferation, or ECM organization. Immunohistochemistry confirmed the expression of the stem cell-related biomarkers NPPA and POSTN in the AVj, further strengthening the hypothesis of the AVj as a specialized microenvironment conducive to stem cell niche activity.